Behavior Transformation during The Covid-19 Pandemic in the Malakok Community of Minangkabau - Cici Nur Azizah; Pebriyenni Pebriyenni (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
The study aims to analyze the form of behavioral transformation during the Covid-19 pandemic among the